Marketing Palavra de Vida: a lógica mercadológica da Assembleia de Deus no Brás - Oliveira , Eliezer Cardoso de (2017)
The researcher's proposal in the elaboration of this dissertation is to work on the questions that involve the problem of breaking paradigms and insertion of multimedia in the largest Pentecostal Church in Brazil: Assemblies of God. More specifically, after analyzing the history of AD, the theme will be delimited in ADBRAS Ministério Madureira, which seems to be avant-garde in contextualizing the sacred, customs and traditional Assembleia music, making use of the various media available in the Brazilian religious market. In the second phase, we intend to work critically, informing about cult and thematic programming options, analyzing the position of religious marketing and its influence on evangelization. The work aims to consolidate itself as bibliographic analysis and field research. . The researcher's dialogue with the theorist, allowed the necessary basis for credibility in the research and formulation of the thesis. This means that the work has been able to go to sources already published in the issues that relate to religious marketing, Pentecostalism and context. It is expected to contribute to the Pentecostal religious segment, in order to present the information and analysis that guides the debate on the use of marketing tools for evangelism, rather than to discuss theological positions, one must know and adapt to the benchmarking of Their processes. The expected results points to the fact that the spread of the new religion of the market, marketing, sociology and theology can go hand in hand. The greatest confirmation of this fact comes from those who created the "Christian" brand one of the most ruthless religious brands of all time.